New Localities and Assessment of the State of Populations of Rare Flora Species (Adonis Vernalis and Pulsatilla Pratensis) in the Chernihiv Region (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Formulation of the problem. Conservation of rare plant species is one of the key challenges of modern ecology, especially under increasing anthropogenic pressure leading to population decline and loss of natural habitats. Insufficient knowledge of the regional distribution of rare species necessitates уточнення their localities and assessment of the current state of their populations. Purpose. To identify new localities of Adonis vernalis L. and Pulsatilla pratensis (L.) Mill. in the Chernihiv region and to assess the state of their populations. Methods. The study was conducted using route survey methods with GPS-based location фиксація, geobotanical description of habitats, counting of individuals, and analysis of population age structure. Regeneration was assessed based on the ratio of pre-generative to generative individuals. Results. New localities of the studied species were identified within meadow-steppe and forest-edge ecotopes. The population of Adonis vernalis comprises approximately 85 individuals and is characterized by relative stability, whereas Pulsatilla pratensis is represented by a smaller population (about 46 individuals) with a fragmented structure. The presence of individuals at different ontogenetic stages indicates ongoing natural regeneration processes. At the same time, the influence of anthropogenic factors on population condition was recorded. Conclusions. The identified localities are important for уточнення the distribution of rare species in the region. The populations are relatively viable but require continuous monitoring and implementation of conservation measures to ensure their stability.
Keywords: rare species; Red Book of Ukraine; plant populations; Adonis vernalis; Pulsatilla pratensis; biodiversity; localities; meadow-steppe communities; ontogenetic structure; nature conservation